Pediatric Chronic Sclerosing Sialadenitis: Kuttner Tumor - Melo, Juliana Carneiro; Kitsko, Dennis; Reyes-Mugica, Miguel (Alliance Communications Group Division Allen Press, 2012)
Chronic sclerosing sialadenitis is an uncommon cause of salivary gland enlargement mainly occurring in the fifth and seventh decade of life. In the Western population, chronic sclerosing sialadenitis has been characterized as an IgG4-related disease. Although rare, this lesion occurs in children. To increase awareness about this entity in the pediatric age group, we report the case of an 11-year-old boy with a hard, 4.0-cm circumscribed mass in the right submandibular gland. Histologically there was marked distortion of the gland architecture by a dense lymphocytic infiltrate and extensive fibrosis with septa that crossed and distorted the gland, leaving atrophic acini and dilated, irregular ducts. The lymphoid infiltrate formed multiple follicles with active germinal centers, numerous plasma cells, and areas with diffuse arrangement. Immunophenotyping showed abundant CD20- and CD3-positive lymphocytes; cytokeratin AE1/AE3 highlighted the distorted architectural pattern; IgG staining showed large numbers of positive cells infiltrating the interstitium and surrounding the atrophic acini and ducts. IgG4 staining revealed a large proportion of positive infiltrating elements. Kuttner tumor belongs to the group of IgG4-related sclerosing diseases. The differential diagnosis includes pleomorphic adenoma and other salivary gland neoplasms. Its recognition in children is important clinically because this entity is amenable to steroid treatment, and additional work up and follow up is warranted to stave off other IgG4-related diseases/complications.
Keywords: Kuttner tumor; pediatric chronic sclerosing sialadenitis